The abolition of the Ottoman Caliphate, 1924
1 online resource.
Keywords: "This book explores the decision by the Grand National Assembly of Turkey in 1924 to abolish the caliphate. The Ottoman sultans had long borne the title of caliphs of Islam, with all the prestigious authority throughout the Muslim world which went with it, and even after the demise of the sultanate in 1922 the caliphate retained great symbolic relevance. The book considers the questions that arose with its abolition, including whether or not the caliphate should be revived, reformed or replaced by other forms of political affiliation and organization. It also assesses related issues concerning identity and legitimate authority, and how to reconcile time-honoured religious institutions and concepts to do with modernity, the nation-state and affiliations of an ethnic and religious nature. Particular topics are also addressed, such as Kurdish-Turkish relations, the divergent views held by deputies in the Grand National Assembly, the pan-Islamic congresses that discussed the fate of the caliphate, and the implications for the British and French empires with their large Muslim populations"--